Lời giải:
Bình phương biểu thức $a$ ta có:
\(a^2=4+\sqrt{10+2\sqrt{5}}+4-\sqrt{10+2\sqrt{5}}+2\sqrt{4^2-(10+2\sqrt{5})}\)
\(=8+2\sqrt{6-2\sqrt{5}}=8+2\sqrt{5+1-2\sqrt{5}}\)
\(=8+2\sqrt{(\sqrt{5}-1)^2}=8+2(\sqrt{5}-1)=6+2\sqrt{5}\)
\(=[\pm (\sqrt{5}+1)]^2\)
Mà $a>0$ nên \(a=\sqrt{5}+1\)
Xét thêm 1 số \(1-\sqrt{5}\)
Ta thấy \(\left\{\begin{matrix} \sqrt{5}+1+1-\sqrt{5}=2\\ (\sqrt{5}+1)(1-\sqrt{5})=-4\end{matrix}\right.\) Do đó, theo định lý Viete đảo thì $a$ là nghiệm của pt \(x^2-2x-4=0\), tức là $a^2-2a-4=0$
Do đó:
\(T=\frac{a^2(a^2-2a-4)-2a(a^2-2a-4)+a^2-2a-4+8}{a^2-2a-4-10a+16}\)
\(=\frac{8}{-10a+16}=\frac{8}{-10(\sqrt{5}+1)+16}=\frac{8}{6-10\sqrt{5}}=\frac{4}{3-5\sqrt{5}}\)